Mild and Efficient One Pot Synthesis of Imidazolinesand Benzimidazoles from Aldehydes - Rajesh Kumar; Y. C. Joshi (E-Journal of Chemistry, 2007)
A series of some imidazolines and benzimidazoles were synthesizedfrom various aldehydes and 1,2-diamines in the presence of ceric(IV)ammonium nitrate (CAN). The title compounds were prepared via one stepsynthesis method. The simplicity of the reaction conditions with shorterreaction time and with out use of column chromatography to get the pureproducts in high yields makes this method more attractive for organic chemists.